Analysis of the Thermoplastic Composite Overmolding Process: Interface Strength - Akkerman, Remko; Bouwman, Mark; Wijskamp, Sebastiaan (Frontiers in Materials, 2020)
Overmolding is a technology in which a thermoplastic composite laminate is thermoformed and subsequently injection overmolded. This near-net-shape manufacturing process is well suited for automated large series production of complex 3D structures with excellent structural performance and a high level of function integration. There is a need for process design tools, which are currently lacking. For this purpose, the bond strength between the overmolded composite laminate and the injected polymer resin was studied by means of process modeling and mechanical testing. Starting from De Gennes' classical reptation theory for reptation and healing of amorphous polymers, an alternative approach was developed to describe the strength development for semi-crystalline materials. A rudimentary description of the degree of melting was implemented to predict the bond strength as a function of the thermo-mechanical history at the interface during forming and subsequent resin injection for PA6 and PEEK, both semi-crystalline matrix materials. Dedicated coupon geometries were developed, manufactured and tested to evaluate the bond strength under tensile and shear loading conditions. Both a single step and a dual step process were evaluated, leading to distinctly different process mechanisms and resulting material structure and mechanical performance of the parts. Suggestions are presented for optimum process conditions and improved design features to further mature this technology.